Contribution Of Childhood To The Personality Development In Khaled Hosseini's And The Mountains Echoed (2013) : A Developmental Psychological Approach - Astuti, Indah Kusuma, Drs. M. Thoyibi, M.S, Mauly Halwat H, Ph. D (2015)
The objectives of the study are to analyze the novel based on its structural elements and to analyze the novel based on Developmental psycological approach. This study is a qualitative study. The object of the study is Khaled Hosseini's And The Mountains Echoed novel published in 2013 in New York by Riverhead Books. The data sources are divided into two, namely primary data source and secondary data source. The primary is the novel itself and the secondary data source is other sources related to the analysis such as the author biography, books of literary theory and also psychology books, particulary related to developmental psychologycal books. The method of data collection is library research. The technique of data analysis is descriptive analysis. Based on psychological analysis, it can be concluded that in this novel, the author illustrates a psychology phenomenon in which an individual is very much influenced by her childhood. It is necessary for her to find out the mystery in her past in order to cope with her present problem.